2019
DOI: 10.15644/asc53/4/3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Clinical and Radiological Parameters in the Evaluation of Molar Furcation Involvement in Periodontitis

Abstract: Usporedba kliničkih i radioloških parametara u procjeni zahvaćenosti furkacije molara kod parodontitisa UvodPrema Američkoj akademiji za parodontologiju, zahvaćenost furkacije jest stanje koje nastaje kada parodontitis zahvati korijen zuba i uzrokuje resorpciju kosti u bifurkacijskom ili trifurkacijskom području višekorijenskoga zuba (1). Opseg oštećenja i položaj marginalnog tkiva u odnosu prema furkaciji daju relevantne kliničke informacije prijeko potrebne za precizniju i pouzdaniju dijagnozu i predvidivu p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…If BW examination was not performed, the distance between CEJ and AC was determined from OPGs ( n = 64). Periodontitis case, stable: <10% BoP, <4 mm PPD (modification of the 2017 classification) Periodontitis case, some inflammation/unstable: ≥10% BoP, ≥4 mm PPD (modification of the 2017 classification) Periodontal health: <10% BoP, ≤3 mm PPD, in non‐periodontitis cases Localized gingivitis: 10–30% BoP, ≤3 mm PPD, in non‐periodontitis cases Generalized gingivitis: >30% BoP, ≤3 mm PPD, in non‐periodontitis cases Tooth loss due to periodontitis: Missing teeth were annotated accordingly if this was considered the most likely cause for tooth loss, that is, cases with limited decay and restorations, few endodontic lesions or root canal treatments, and where the general bone level in the remaining dentition suggested periodontal tooth loss. Bone loss plausible by reasons other than periodontitis: Localized bone loss in proximity to impacted teeth or reduced bone level in areas adjacent to missing teeth was disregarded in the evaluation of the periodontitis cases. Complexity: All complexity factors of the 2017 classification were considered. The following complexity factors were defined: Vertical bone loss: Radiographic defects ≥3 mm deep and ≤3 mm wide. Furcation grade ≥2: Overt radiolucency evident in the furcation areas (Zhang et al, 2018; Komšić et al, 2019). Bite collapse/drifting/flaring: ≥3 teeth with obvious change of position and/or mobility grade ≥2 within the same sextant, in combination with presence of periodontal bone loss likely to cause this condition. PPD >5 mm was used to identify Stage III when the radiographic bone level corresponded to Stage II definition. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If BW examination was not performed, the distance between CEJ and AC was determined from OPGs ( n = 64). Periodontitis case, stable: <10% BoP, <4 mm PPD (modification of the 2017 classification) Periodontitis case, some inflammation/unstable: ≥10% BoP, ≥4 mm PPD (modification of the 2017 classification) Periodontal health: <10% BoP, ≤3 mm PPD, in non‐periodontitis cases Localized gingivitis: 10–30% BoP, ≤3 mm PPD, in non‐periodontitis cases Generalized gingivitis: >30% BoP, ≤3 mm PPD, in non‐periodontitis cases Tooth loss due to periodontitis: Missing teeth were annotated accordingly if this was considered the most likely cause for tooth loss, that is, cases with limited decay and restorations, few endodontic lesions or root canal treatments, and where the general bone level in the remaining dentition suggested periodontal tooth loss. Bone loss plausible by reasons other than periodontitis: Localized bone loss in proximity to impacted teeth or reduced bone level in areas adjacent to missing teeth was disregarded in the evaluation of the periodontitis cases. Complexity: All complexity factors of the 2017 classification were considered. The following complexity factors were defined: Vertical bone loss: Radiographic defects ≥3 mm deep and ≤3 mm wide. Furcation grade ≥2: Overt radiolucency evident in the furcation areas (Zhang et al, 2018; Komšić et al, 2019). Bite collapse/drifting/flaring: ≥3 teeth with obvious change of position and/or mobility grade ≥2 within the same sextant, in combination with presence of periodontal bone loss likely to cause this condition. PPD >5 mm was used to identify Stage III when the radiographic bone level corresponded to Stage II definition. …”
Section: Methodsmentioning
confidence: 99%
“…Complexity: All complexity factors of the 2017 classification were considered. The following complexity factors were defined: Vertical bone loss: Radiographic defects ≥3 mm deep and ≤3 mm wide. Furcation grade ≥2: Overt radiolucency evident in the furcation areas (Zhang et al, 2018; Komšić et al, 2019). Bite collapse/drifting/flaring: ≥3 teeth with obvious change of position and/or mobility grade ≥2 within the same sextant, in combination with presence of periodontal bone loss likely to cause this condition. PPD >5 mm was used to identify Stage III when the radiographic bone level corresponded to Stage II definition. …”
Section: Methodsmentioning
confidence: 99%
“…Similar results were also described by Qiao et al 20 , who reported significant agreement in the diagnosis of FI by ISE. Moreover, the study by Zhang et al 25 , CBCT showed more significant agreement in the detection of distal sites by clinical evaluation, while in the recent study by Komšić, et al 15 , the buccal site was better diagnosed than the distal and mesial sites.…”
Section: Discussionmentioning
confidence: 93%
“…CBCT is highly accurate for detecting furcation involvement, and has been extensively used for challenging diagnoses, such as Degree I or II 12,13 . In vivo studies 3,5,10,14,15 have shown the potential of 3D images compared to intra-surgical assessments for diagnosing FI in maxillary molars, but results are controversial regarding CBCT accuracy for this purpose. The aim of this study was therefore to compare CBCT images with clinical and intrasurgical analyses to diagnose maxillary molar furcation involvement.…”
Section: Introductionmentioning
confidence: 99%
“…The radiographic gold standard for diagnosing FI is CBCT. A diverse number of studies compared CBCT with presurgical and intra surgical (IS) measurements and found CBCT having agreeable or better accuracy compared to probing and intra-surgical measurements [12][13][14][15]. RadioVisioGraphy (RVG) is a 2D digital imaging aid that projects the image directly in the monitor.…”
Section: Introductionmentioning
confidence: 99%